Analysis of Human Resource Management in Madrasah: A Case Study in Indonesia - Supriatna, Dasep (AGUSPATI Research Institute, 2025)
This study analyzes Human Resource Management (HRM) practices within Indonesian madrasahs[4] using a qualitative embedded multiple-case study design. Guided by the Resource-Based View (RBV)[1], it investigates how HRM functions like recruitment, training, and performance management contribute to developing human resources as valuable, rare, inimitable, and non-substitutable (VRIN)[2] assets. Findings reveal practices aim to cultivate unique staff competencies aligned with the madrasahs' distinct religious mission, leveraging human capital for institutional effectiveness. However, resource constraints and inconsistencies challenge the systematic development and retention of these strategic assets.